1991
DOI: 10.1097/00004032-199102000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Suggested Reference Values for Regional Blood Volumes in Humans

Abstract: Estimates of regional blood volumes (BVs) in man are needed for the dosimetry of radionuclides that decay in the circulation to a significant extent. The tabulation of regional BVs in Publication No. 23 of the International Commission on Radiological Protection (ICRP Reference Man document) may be the best available for dosimetric applications but is not consistent with current information for some organs and does not address some important blood pools. The purpose of this paper is to suggest an improved set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…The percentage of blood volume in the spleen has been reported to be between 20% and 40% from studies in rats 18 and humans. 19 We estimate that the blood accounts for 10% to 15% of the total radioactivity measured in one gram of spleen (using as reference the cpm/g in the spleen of CH3397 [ Table 2] and the radioactivity measured in the blood of the same animal of 2.1 ϫ 10 6 cpm/mL). Thus, by subtracting the aforementioned 2 contributions of nonspecific uptake (between 20% and 25%), we estimate approximately 1.1 ϫ 10 9 CD4 ϩ cells per gram of spleen of CH3397.…”
Section: Number Of Cd4 ؉ Lymphocytes In the Bodymentioning
confidence: 99%
“…The percentage of blood volume in the spleen has been reported to be between 20% and 40% from studies in rats 18 and humans. 19 We estimate that the blood accounts for 10% to 15% of the total radioactivity measured in one gram of spleen (using as reference the cpm/g in the spleen of CH3397 [ Table 2] and the radioactivity measured in the blood of the same animal of 2.1 ϫ 10 6 cpm/mL). Thus, by subtracting the aforementioned 2 contributions of nonspecific uptake (between 20% and 25%), we estimate approximately 1.1 ϫ 10 9 CD4 ϩ cells per gram of spleen of CH3397.…”
Section: Number Of Cd4 ؉ Lymphocytes In the Bodymentioning
confidence: 99%
“…It has been demonstrated by many investigators with MR and PET that the total cerebral blood volume including arterial and venous blood pools is approximately 2% to 3% and 4% to 5% for the white matter and gray matter, respectively (Grubb et al, 1973;Sakai et al, 1985;Perlmutter et al, 1987;Brooks et al, 1985;Leggett andWilliams, 1991, Kuppusamy, 1996). Although a wide range of the ratio of cerebral venous blood volume to the total cerebral blood volume has been reported (0.75 to 0.85) in the literature (Tomita et al, 1978;Tomita, 1988), Pollard et al (1996a,b) recently demonstrated that a ratio of 0.75 would be a reasonable choice under normal physiologic conditions.…”
Section: Effects Of Other Paramagnetic Sources and Magnetic Field Varmentioning
confidence: 99%
“…However, the main drawback is that the amount of deoxyhemoglobin-induced signal loss relies largely on the available blood volume. Because it has been demonstrated that the normal cerebral blood volume (CBV) in the brain parenchyma ranges between 2% to 5% (Grubb et al, 1973;Sakai et al, 1985;Perlmutter et al, 1987;Brooks et al, 1985;Leggett and Williams, 1991;Lin et al, 1997), it may lead to poor signal-to-noise for this approach. In contrast, the signal model proposed by Yablonskiy and Haacke (1994) focuses on deoxyhemoglobin-induced signal loss outside of the intravascular space, which could potentially be more easily detected with a gradient echo imaging approach.…”
mentioning
confidence: 99%
“…Based upon previous measurements and estimates of Q, C024. [35][36][37][38], this model parameter was expected to vary within the bounds of 0.04-0.17. A search range for values of V max x was defined using the observation by We therefore expected maximal extrahepatic rate of metabolism to range from 0-70% of that in the liver.…”
Section: Physiologically-based Modelmentioning
confidence: 99%
“…Two of these 66 values were below the expected physiologic range of 0.04-0.1724. [35][36][37][38]; for one of these two subjects only limited data (1 breath, 2 blood samples) were available in the terminal phase, where adipose blood flow is most influential. The model was able to explain 94 ± 2.7% (range, 85-98%) of the 'H8-toluene data variability, and 90 ± 6.5% (range, 68-98%) of the 2H8-toluene data variability in the 33 exposure sets.…”
Section: Optimized Model Parametersmentioning
confidence: 99%